Artificial neural network based sensorless position estimation and direct torque control for stepper motor - Arise, Nagasridhar; Babu, Thiruveedula Madhu; Gollapudi, Srinidhi; Dommeti, Tarun Kumar; Kummari, Abhishek; Shambukari, Mahith (International Journal of Advances in Applied Sciences, 2025)
This study describes and illustrates how sensorless location estimation is achieved through the application of artificial neural network (ANN) control. Control stepper motor torque directly. Using stepper motors directly leads to a lot of problems; therefore, automated control systems are now commonly preferred. Stepper motors have several drawbacks when used directly, including the potential for steps to occasionally be missing while the motors are running. When physical sensors are not available, the proposed method estimates rotor position and speed using electrical signals and ANN algorithms. Simulation and experiment results demonstrate accurate position estimation (±1.5°) and efficient torque control. The sensorless direct torque control (DTC)-ANN approach increases the performance, reliability, and cost of stepper motors in robotics, computer numerical control (CNC) machines, and 3D printing.